IntelliOrder” - Intelligent Speech Recognition Self-Ordering Management System for Restaurants - Muhammad Daniel Vineshen; Khairunnisha Zainal, Nur; Helen Joseph, Minnu (International Journal of Psychosocial Rehabilitation, 2019)
This paper proposes a software system that simplifies the way orders are taken in a restaurant by developing a self-ordering system that is equipped with voice recognition that is able to capture the customer’s native language and translate it into the default language of the system. Moreover, the software system provides the capability of splitting bills for respective customers under the same table to save the hassle for the customers to split it among themselves. Furthermore, the software system will interconnect between multiple interfaces that will be used by six major users which are the customers, cooks, cashier, servers, managers/owners and administrator. Each of the users will be restricted to functionalities that are designated for them.